Takhrij and Syarah Hadith of Agrotechnology: Agarwood in Covid-19 Treatment - Muhamad Ariq Ranadipraja; Wahyudin Darmalaksana; Dikayani Dikayani (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this research is to discuss the hadith of the Prophet (peace and blessings of Allaah be upon him) about the plants of Agarwood. This research method is qualitative through takhrij and syarah hadith approach with agrotechnology analysis. The result and discussion of this research is that Agarwood has many benefits, but there has been no further research on whether Agarwood can treat Corona Virus. The conclusion of the research is takhrij and syarah hadits Prophet Saw. about Agarwood plants with agrotechnology analysis, this plant has many benefits especially in the health sector.